1999
DOI: 10.1143/jjap.38.2194
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Ru and Its Application in (Ba,Sr)TiO3 Capacitors for Future Dynamic Random Access Memories

Abstract: Ru films were fabricated by chemical vapor deposition using Ru(C 5 H 5 ) 2 and O 2 . The deposition of Ru film was controlled by the surface reaction kinetics as the rate limiting step with activation energy of 2.48 eV below 250 • C and by the mass transport process above 250 • C. Ru films had a polycrystalline structure and showed low resistivity of about 12 µ cm. Ru films deposited at 230 • C showed excellent step coverage. We applied Ru films prepared by chemical vapor deposition to the bottom electrode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…Increased surface roughness with increasing deposition temperature and film thickness has also been reported for ruthenium films grown by CVD. [2] The results from the TOF-ERDA indicated that the films were very pure. The impurity content of the ruthenium films grown at temperatures of 300 C, 350 C, and 400 C is shown in Table 1.…”
Section: Film Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased surface roughness with increasing deposition temperature and film thickness has also been reported for ruthenium films grown by CVD. [2] The results from the TOF-ERDA indicated that the films were very pure. The impurity content of the ruthenium films grown at temperatures of 300 C, 350 C, and 400 C is shown in Table 1.…”
Section: Film Propertiesmentioning
confidence: 99%
“…CVD is preferred in applications where high conformality of the films is needed. Precursors such as RuCp 2 [2,16,17] (Cp = cyclopentadienyl), Ru(acac) 3 [17,18] (acac = acetylacetonate), Ru-(thd) 3 [19] (thd = 2,2,6,6-tetramethyl-3,5-heptanedionate), Ru(hfb)(CO) 4 [20] (hfb = hexafluoro-2-butyne), and Ru 3 -(CO) 12 [17] are, for example, available for the CVD of ruthenium thin films. However, these precursors are not ideal for CVD due to their high melting points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the deposition of Ru films by MOCVD is documented in the literature, [7,[9][10][11][12][13][14][15][16][17][18][19][20] the development of an MOCVD process for large-scale manufacture is primarily restricted by the availability of a suitable precursor, which needs to be highly volatile, thermally stable, and inexpensive. For example, it was reported [9] that Ru films prepared using bis(cyclopentadienyl)ruthenium (Ru(Cp) 2 ) showed low resistivity, small tensile stress, and excellent step coverage.…”
Section: Introductionmentioning
confidence: 99%
“…New high-dielectric constant materials, such as tantalum pentoxide (Ta 2 O 5 ), [1,2] and barium strontium titanate [(Ba,Sr)TiO 3 ], [3,4] are expected to be used as capacitor materials for gigabit-generation dynamic random access memory (DRAM) devices. Ru is used as an electrode for these dielectric materials due to its dry etchability and high conductivity under oxidizing conditions.…”
Section: Introductionmentioning
confidence: 99%